Fighting at the legal boundaries : controlling the use of force in contemporary conflict - Watkin, Kenneth (New York, NY : Oxford University Press, 2016)
'Fighting at the Legal Boundaries' offers a holistic approach towards the application of the various constitutive parts of international law. The author focuses on the interaction between the applicable bodies of law by exploring whether their boundaries are improperly drawn, or are being interpreted in too rigid a fashion. Emphasis is placed on the disconnect that can occur between theory and practice regarding how these legal regimes are applied and interact with one another.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 7, 2016).
Keywords: Aggression (International law); War (International law); Self-defense (International law); Combatants and noncombatants (International law); Non-state actors (International relations); Preemptive attack (Military science); Law; International law